Physical, structural and optical properties of bio-silica borotellurite glass system doped with samarium oxide nanoparticles - Asyikin, A. S.; Halimah, M. K.; Latif, A. A.; Faznny, Mohd Fudzi; Nazrin, S. N. (Elsevier Science, Ltd., 2020)
Glasses with chemical composition {[(TeO₂)0.7 (B₂O₃)0.3]0.8 [SiO₂]0.2}1-x Sm₂O₃ NPsx where x = 0.01 to 0.05 molar fraction have been fabricated using conventional melt-quenching method. Fourier transform infrared (FTIR) spectra reveal the presence of TeO3, SiO2 and BO3 structural units in the glass network. The existence of samarium oxide nanoparticles was recorded through high resolution transmission electron microscopy (HRTEM) with particle size of 71.74 nm. Meanwhile, the optical properties of fabricated samples were determined by UV–vis analysis. The variation in the optical band gap identifies the modification in the glass network to the formation of bridging oxygen (BO) and non-bridging oxygen (NBO). Other optical parameter including refractive index, Urbach energy, electronic polarizability, oxide ion polarizability and optical basicity were determined. The metallization criterion values obtained is in the range of 0.403 to 0.409, which suggest that the glass material has a huge potential applications, in non-linear optics fields.